An improved method for determining dermal exposure to polycyclic aromatic hydrocarbons - Strandberg, Bo; Julander, Anneli; Sjöström, Mattias; Lewné, Marie; Hatice, Koca Akdeva; Bigert, Carolina (Chemosphere (Oxford), 2018)
Many workers are occupationally exposed to polycyclic aromatic hydrocarbons (PAHs), which may cause various health problems, and some PAHs are known or suspected carcinogens. PAH exposure is primarily monitored by air sampling, but contamination may also occur through dermal exposure. PAHs adsorbed to the skin can be sampled by tape-stripping, but subsequent extraction of sampling tapes in organic solvent also releases diverse co-eluting substances that are difficult to remove before analysis of the PAHs by gas chromatography/mass spectrometry (GC/MS). The objective of this study was to optimise a procedure for analytical clean-up after extraction of 32 PAHs from tape-strips, by dialysis in organic solvent using semipermeable membranes. With triplicate subsamples, the developed method yields acceptable precision and repeatability for both the 32 PAHs, across the concentration range 10–160 ng per sample, and for a certified reference material (urban dust). The optimized clean-up procedure and GC/MS methodology was used to assess PAHs on skin from the lower part of the ventral side of the wrist and just below the collar bone of three firefighters and seven controls (office workers). Several gaseous and particle-bound PAHs were detected in all samples, including controls. Thus, the optimized procedure using semipermeable membranes for clean-up of tape-strip extracts can be used to assess the dermal exposure of both occupational and general populations to multiple PAHs. The results also show that both gaseous and particle-bound PAHs, including alkylated species, may be present on skin. •The procedure can clean-up tape-strips to assess dermal exposure to multiple PAHs.•The procedure is simple, non-destructive and gives clean extracts for GC/MS analysis.•The method can be used in working exposure situations and in the general population.•Both gaseous and particle-bound PAHs, including alkylated species, could be detected.